Studies on the effects of Posterior Amputation on the Cerebral Neurosecretory Cells of Indian Earthworm, Lampito mauritii (Kinberg) - Anurag Bhattacharjee; P. S. Chaudhuri (New Frontiers in Medicine and Medical Research Vol. 11, 2021)
Background: Earthworms are subjected to predator attacks and agricultural practices and thus nature has gifted them the power of restoration of lost body segments. In absence of discrete nonneural endocrine gland, the cerebral neurosecretory system probably plays an important role in wound healing and regeneration of lost body segments. Aim: Present paper deals with studies on cytomorphological changes in the cerebral neurosecretory cells following posterior amputation in topsoil Indian earthworm species, Lampito mauritii. Method: Following posterior amputation of earthworm with paragon knife, dissected cerebral ganglia were fixed in Bouin’s fluid and processed for conventional neurosecretory staining techniques: Paraldehyde Fuchsin (AF) and Chrome Alum Haematoxylin Phloxin (CAHP). Result: Wave of muscular contraction along the anteroposterior direction of the body of Lampito mauritii was recorded following transection of 10 posterior most body segments. In contrast to control, cerebral neurosecretory cells (particularly the AF+ve A cells) displayed changes in the secretory dynamics following posterior amputation of body segments. During healing up of wounds after 24 hours, there was a drop in the number of AF+ve A cells due to depletion of neurosecretory materials. Formation of regeneration blastema during 48 to 72 hours of amputation was accompanied by rise in number of AF+ve deeply stained A neurosecretory cells. The moderately stained B cells also showed accumulation of coarse secretory granules. Axonal transport along with ‘zone of accumulation’ charged with AF+ve neurosecretion were also interesting observations after 48 to 72 hours of amputation. Conclusion: Our preliminary study indicates cerebral neurosecretory cells are involved in the healing up of wounds and subsequent regeneration in earthworm, Lampito mauritii.